Application of central composite design to reveal resin deterioration during the removal of hexavalent chromium from wastewater - Xiao, Ke (Environmental technology, 2021)
As a strong oxidant, aqueous Cr(VI) possibly oxidizes the polymer resin and weakens resin adsorption property during Cr(VI) removal from solutions by ion exchange. In the present study, to minimize the resin oxidation, central composite design approach based on response surface methodology was employed with different variables (Cr(VI) concentration of 100-1000 mg L-1, temperature of 293-333 K, pH of 1-7, and reaction time of 0-120 min) using a strong anionic resin (D202). The pH and reaction time had the most significant effect on resin oxidation, followed by Cr(VI) concentration. The temperature had a comparatively less significant effect on resin oxidation. The minimal Cr(VI) reduction efficiency (0.4%) was achieved with a Cr(VI) concentration of 251.5 mg L-1, temperature of 323.1 K, pH of 6.2 and reaction time of 52.5 min. Based upon a long-term operation and Fourier transform infrared rays analyses, the oxidation pathway of D202 resin was proposed. The rupture of the C-N bond led to the disappearance of the nitrogen-containing functional groups, which resulted in a significant decrease of resin exchange capacity